Offshoring and Labour Market Reforms: Modelling the German Experience - Thomas Beissinger; Nathalie Chusseau; Joël Hellier (Institute for the Study of Labor (IZA), 2015)
A usual interpretation of the high performance of the German economy since 2005 is that the Hartz labour market reforms have boosted German competitiveness, resulting in higher exports, higher production and lower unemployment. This explanation is at odds with the sequence of observed facts. We propose and model an alternative scenario in which offshoring explains the gains in competitiveness but increases unemployment and inequality, and the subsequent labour market reforms lower unemployment by lessening the reservation wage and expanding the non-tradable sector. The model replicates the developments of the German economy since 1995: 1) Germany offshores more intensively than other advanced countries; 2) The increase in competitiveness and in the exports/production ratio occurs before the implementation of the labour market reform, and this comes with both higher inequality and higher unemployment; 3) The implementation of the reform reduces unemployment, but also decreases the exports/production ratio and increases inequality. The model also predicts that the reduction in unemployment in Germany would have occurred without the Hartz reforms, but later and less intensively. We finally discuss the possible extension of this 'strategy' to other Eurozone countries, and alternative policies that activate similar mechanisms without increasing inequality.
Keywords: H55; J31; J65; 330; Germany; inequality; labour market reform; offshoring; unemployment